Changing discourses in Aboriginal and Torres Strait Islander health research, 1914‐2014. (7th July 2014) - Thomas, David P; Bainbridge, Roxanne; Tsey, Komla
Summary: Aboriginal and Torres Strait Islander people strongly assert that health research has contributed little to improving their health, in spite of its obvious potential. The health concerns of Aboriginal and Torres Strait Islander people were largely ignored in early research published in the MJA, which reflected broader colonial history and racial discourses. This began to change with the demise of scientific racism, and changed policies and political campaigns for equal treatment of Indigenous people after the Second World War. In response to pressure from Aboriginal and Torres Strait Islander people and organisations, in parallel to broader political struggles for Indigenous rights since the 1970s, there have been significant and measurable changes to Aboriginal and Torres Strait Islander health research. Many of these changes have been about the ethics of health research. Increasingly, Aboriginal and Torres Strait Islander researchers, communities and organisations are now controlling and decolonising health research to better meet their needs, in collaboration with non‐Indigenous researchers and research organisations.